On the Provision of Advanced Telecommunication Services in Rural Areas - Lambrinos, Lambros (My University, 2012)
Even though in many parts of the world people enjoy the features of modern telecommunication services, a significant number of inhabitants in rural areas are deprived of access to such facilities. In this text we propose how we can utilize existing technologies for the provision of telecommunication facilities in rural areas: IP telephony based upon open source software and off-the-shelf hardware and voice messaging based upon the Delay Tolerant Networking paradigm.
Keywords: Open source software; Internet telephony; Telephone systems; Telecommunications.